PENENTU KEPUASAN KERJA AUDITOR - Ceacilia Srimindarti; Rr. Tjahjaning Poerwati; Pancawati Hardiningsih; Gregorius Anggana Lisiantara; Rachmawati Meita Oktaviani (Dinamika Akuntansi Keuangan dan Perbankan, 2025)
This study aims to examine the effect of role conflict and locus of control on auditors’ job satisfaction. The population in this study consists of auditors working at Public Accounting Firms in the city of Semarang. The respondents selected for this research are auditors who work at Public Accounting Firms in Semarang and have at least one year of work experience. Data collection was conducted using a convenience sampling technique through questionnaires. Multiple regression analysis was used as a tool for data analysis. The results of the study show that role conflict has a negative effect on job satisfaction, whereas locus of control has a positive effect on job satisfaction.